2022
DOI: 10.1155/2022/7272371
|View full text |Cite
|
Sign up to set email alerts
|

Qinbaohong Zhike Oral Liquid Attenuates LPS-Induced Acute Lung Injury in Immature Rats by Inhibiting OLFM4

Abstract: Acute respiratory infections (ARIs) are a common public safety threat with high morbidity and mortality in pediatric patients worldwide. Qinbaohong Zhike oral liquid (QBH), a marketed traditional Chinese medicine product, has been widely used to cure respiratory diseases. QBH is reported to have antitussive, expectorant, and antiasthmatic properties. However, its treatment effect against ARIs is not elucidated. This study aimed to explore the therapeutic efficacy of QBH in the treatment of ARIs-induced pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…OLFM4, an important regulator of inflammatory and immune responses, is highly expressed in various inflammatory diseases ( 17 ). In an LPS-challenge rat model, blockage of OLFM4 expression was confirmed to mitigate lung tissue damage and hyperinflammatory response ( 18 ). Additionally, Higher percentages of OLFM4 + neutrophils were shown to be associated with worsening clinical outcomes in patients with sepsis, blunt traumatic injuries, and ARDS ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…OLFM4, an important regulator of inflammatory and immune responses, is highly expressed in various inflammatory diseases ( 17 ). In an LPS-challenge rat model, blockage of OLFM4 expression was confirmed to mitigate lung tissue damage and hyperinflammatory response ( 18 ). Additionally, Higher percentages of OLFM4 + neutrophils were shown to be associated with worsening clinical outcomes in patients with sepsis, blunt traumatic injuries, and ARDS ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TNF‐α, IL‐1β, and IL‐8 are important pro‐inflammatory mediators in inflammatory responses, moreover, excessive release of the pro‐inflammatory cytokines play crucial roles in the pathogenesis and development of ALI. 21 , 22 , 23 CCNB1 and CDC2 are known to be important cell cycle regulatory proteins, and play key roles in promoting cell cycle progression. 24 , 25 Caspases, especially caspase‐3 and caspase‐9, are considered as crucial effectors of cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation assay by CCK‐8 as well as cell cycle and cell apoptosis analysis by flow cytometry showed that LPS administration significantly decreased cell proliferation, resulted in cell cycle arrest at G1 phage, and elevated apoptosis rate of A549 cells. It has been reported that TNF‐α, IL‐1β, and IL‐8 are important pro‐inflammatory mediators in inflammatory responses, moreover, excessive release of the pro‐inflammatory cytokines play crucial roles in the pathogenesis and development of ALI 21–23 . CCNB1 and CDC2 are known to be important cell cycle regulatory proteins, and play key roles in promoting cell cycle progression 24,25 .…”
Section: Discussionmentioning
confidence: 99%